Pengaruh Pengembangan Karir Dan Disiplin Terhadap Motivasi Kerja PD. BPR Artha Sukapura Cabang Salopa - Muthia Dwi Fatma Utami; Enas Enas; Aan Anwar Sihabudin (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The research was carried out with the aim of knowing the impact of Career development and discipline on work motivation of PD. BPR Artha Sukapura Salopa branch. The problem of employee work motivation at PD BPR Artha Sukapura Salopa Branch is not optimal, it occurs from career development which is relatively difficult and discipline is still lacking causing employees to be less motivated at work, according to (Bukhori & Dewi, 2018) with a high level of employee work discipline it will Motivate employees to carry out their work well, which will indirectly increase employee performance. The method used in this research is quantitative descriptive. Research results: 1. Career development has a positive and significant effect on work motivation. This means that if career development increases, work motivation will also increase. 2. Work discipline has a positive and significant effect on work motivation. This means that if Work Discipline increases, then Work Motivation will also increase. 3. Career Development and Work Discipline have a positive and significant effect on Work Motivation. This means that if career development and work discipline increase, then work motivation will also increase.